Super- ja thomasfosfaatti rahkasuon lannoitteina - Takala, Mauri (Agricultural and Food Science, 1961)
At Leteensuo Experiment Station a trial to compare the effects of superphosphate and basic slag on Sphagnum soil was started in 1926. The test area consisted of a Sphagnum fuscum pine bog. The thickness of the unhumified Sphagnum peat layer was about 2 metres. Under this layer there is a layer of Sphagnum-Carex peat and Carex peat so that the thickness of the whole peat layer is more than 3 metres. The test area was reclaimed in summer 1924 and clayed in winter 1926 (200 m3/ha). It was ditched leaving the strips between the open ditches 20 metres wide. The test area contains 2 strips. In 1926—27 the test area was treated with stable manure and fen peat in equal amounts, altogether 50 m3/ha. Manuring was renewed with similar amounts in 1935. One of the strips was limed with slaked lime 4000 kg/ha in 1926–27, 2000 kg/ha in 1935 and with limestone dust 2000 kg/ha in 1940. Basic slag was applied in amounts containing citric acid soluble P2O5 in the same ratio as the superphosphate contained ammonium citrate soluble P2O5. The whole test area was treated yearly with 40 % potassium salt 250 kg/ha and with calcium nitrate 200–300 kg/ha. The original plan was changed so that in 1940, 1942 and 1949—52 the test area was not treated with phosphate fertilizers. In 1948 the basic slag was replaced by a corresponding amount of hyperphosphate. The test results starting from 1948 are shown separately in Table 5. According to the test results the effect of superphosphate on cereals and ley on Sphagnum bog was better than the effect of basic slag. Superphosphate improves the quality of the crop more than basic slag and has a favourable effect among others on the growth of leguminous plants.